Hepatectomy in a case of hepatocellular carcinoma with constitutional indocyanine green excretory defect. (2018) - Nakatake, Richi; Ishizaki, Morihiko; Miyasaka, Chika; Matsui, Kosuke; Kaibori, Masaki
Highlights: Constitutional indocyanine green excretory defect is extremely rare. The ICGR15 is important for estimating hepatic functional reserve and selection of the appropriate surgical procedure. Because of the rarity of constitutional ICG excretory defect, its clinical features are not well understood. At present, the indications for surgery for this condition should be comprehensively considered. Findings of liver function tests, such as a general liver function test and GSA liver scintigraphy, are important for treating this disorder. Abstract: Introduction: Constitutional indocyanine green (ICG) excretory defect is extremely rare. The indocyanine green retention rate at15 min (ICGR15) is important for estimating hepatic functional reserve and selection of the appropriate surgical procedure before hepatectomy is performed. Because of the rarity of constitutional ICG excretory defect, its clinical features are not well understood. We report here evaluation and treatment of a patient with such a disorder. Presentation of case: An 83-year-old man was admitted to hospital with the diagnosis of resectable hepatocellular carcinoma. The preoperative indocyanine green (ICG) retention rate at 15 min was greater than 76.2%. Despite this finding, Child–Pugh classification and 99m Tc-galactosyl human serum albumin (GSA) liver scintigraphy didn't show any abnormal findings, and there was no background disease. Therefore, we diagnosed him with constitutional ICG excretory defect and performed partial hepatectomy. For patients requiring hepatectomy with this disease the indications and procedure for surgery should be considered. These should be based on liver function tests such as GSA liver scintigraphy. Conclusions: Constitutional ICG excretory defect is an extremely rare disorder. At present, the indications for surgery for this condition should be comprehensively considered. Findings of liver function tests, such as a general liver function test and GSA liver scintigraphy, are important for treating this disorder.